As Luzes do Príncipe. Sobre as experiências realizadas na Ilha do Príncipe em 1919, que ajudaram a validar a Teoria da Relatividade Geral - Rui Tavares (Outros Títulos, 2019)
By creating this comic, Living Science joins the celebrations of the 100th anniversary of the expeditions to the island of Príncipe in São Tomé e Príncipe, and Sobral, in Brazil, which allowed proof of the theory of General Relativity previously predicted by Albert Einstein. This comic will be disseminated and distributed on a large scale and aims to the presentation of the theory of General Relativity, using language understandable throughout the public. In addition, it is intended that the general public be able to value the expeditions made to Island of Príncipe and Sobral by astronomers portrayed here.